Analisis Kejadian Hipertensi Pada Wanita Menopause di Wilayah Kerja Puskesmas Lok Batu - Roseyanti, Ika Rena; Iswandari, Novita Dewi; Hasanah, Siti Noor (Pusat Riset dan Inovasi Nasional, 2024)
Menopausal women have a higher risk of hypertension than those who have not been menopausal. Hypertension can damage organs and cause stroke, kidney failure and heart attack. The purpose of the study was to determine the incidence of hypertension in menopausal women in the Working Area of the Lok Batu Health Center. This research method uses quantitative analytical surveys with a cross sectional approach. The population is all menopausal women in the Working Area of Lok Batu Health Center as many as 156 people with purposive sampling techniques as many as 61 respondents. Chi square data analysis technique. The results showed that the majority of the incidence of level 2 hypertension was 33 respondents (54.1%), hormonal birth control history was 42 respondents (68.9%), normal BMI was 33 respondents (54.1%), basic education was 57 respondents (93.4%), working as many as 40 respondents (65.6%). The results of statistical tests using chi square had no relationship between family planning history p = 0.531 (p > 0.05), body mass index p = 0.458 (p > 0.05), education p = 0.403 (p > 0.05) and work p = 0.399 (p > 0.05) with the incidence of hypertension in menopausal women in the working area of the Lok Batu Health Center.